PERANCANGAN MOTIF DEKORATIF PASIR BERBISIK PADA BUSANA READY TO WEAR - Agni Agustin; Sari Yuningsih (Corak : Jurnal Seni Kriya, 2021)
Indonesia's diverse natural wealth is very interesting to browse and explore. One of the interesting phenomena is Pasir Berbisik and Edelweiss flowers on Mount Bromo, Malang, East Java. Pasir Berbisik comes from the phenomenon when the wind blows and grains of sand fly and sounds like a whisper in everyone's ear passing by, this phenomenon has an interesting and unique visualization to be used as a decorative element in clothing. In this study, these uniqueness will be explored with various textile decorative techniques to produce ready-to-wear designs, inspired by Pasir Berbisik and Edelweiss flowers. The result of this study is a collection of ready-to-wear clothing inspired by Pasir Berbisik and Edelweiss flowers with Tie dye and embroidery techniques. With this collection, it is hoped that it can provide a new alternative in the development of ready-to-wear clothing for academics or fashion practitioners. Kekayaan alam Indonesia yang beragam sangat menarik untuk ditelusuri dan diekplorasi. Salah satu fenomena yang menarik, yaitu pasir berbisik dan bunga Edelweis di Gunung Bromo, Malang, Jawa timur. Pasir berbisik berasal dari fenomena ketika angin bertiup lalu butiran-butiran pasir beterbangan dan terdengar seperti bisikan di telinga setiap orang yang melewatinya. Fenomena tersebut memiliki visualisiasi yang menarik dan unik untuk dijadikan salah satu elemen dekoratif pada busana. Pada kajian ini, keunikan tersebut akan diekplorasi dengan berbagai teknik dekoratif tekstil untuk menghasilkan rancangan busana siap pakai, dengan inspirasi pasir berbisik dan bunga Edelweis. Hasil dari kajian ini berupa koleksi busana siap pakai dengan inspirasi pasir berbisik dan bunga Edelweis dengan teknik tie dye dan bordir. Dengan koleksi tersebut diharapkan dapat memberikan alternatif baru dalam pengembangan busana siap pakai bagi akademisi atau praktisi bidang fesyen.